The Role of Awareness on Motor-Sensory Temporal Recalibration - Bubna, Mikaela; Lam, Melanie Y.; Cressman, Erin K. (Frontiers in Integrative Neuroscience, 2022)
Temporal recalibration (TR) may arise to realign asynchronous stimuli after exposure to a short, constant delay between voluntary movement and sensory stimulus. The objective of this study was to determine if awareness of the temporal lag between a motor response (i.e., a keypress) and a sensory event (i.e., a visual flash) is necessary for TR to occur. We further investigated whether manipulating the required motor and perceptual judgment tasks modified the influence of awareness on TR. Participants (n = 48) were randomly divided between two groups (Group 1: Aware and Group 2: Unaware). The Aware group was told of the temporal lag between their keypress and visual flash at the beginning of the experiment, whereas the Unaware group was not. All participants completed 8 blocks of trials, in which the motor task (single or repetitive tap), perceptual judgment task (judging the temporal order of the keypress in relation to the visual flash or judging whether the two stimuli were simultaneous or not), and fixed temporal lag between keypress and visual flash (0 ms or 100 ms) varied. TR was determined by comparing judgments between corresponding blocks of trials in which the temporal lag was 0 ms and 100 ms. Results revealed that both the Aware and Unaware groups demonstrated a similar magnitude of TR across all motor and perceptual judgment tasks, such that the magnitude of TR did not vary between Aware and Unaware participants. These results suggest that awareness of a temporal lag does not influence the magnitude of TR achieved and that motor and perceptual judgment task demands do not modulate the influence of awareness on TR.